2020
DOI: 10.1093/mnras/staa466
|View full text |Cite
|
Sign up to set email alerts
|

Two new double-lined spectroscopic binary white dwarfs

Abstract: We present radial velocity observations of four binary white dwarf candidates identified through their over-luminosity. We identify two new double-lined spectroscopic binary systems, WD 0311−649 and WD 1606+422, and constrain their orbital parameters. WD 0311−649 is a 17.7 h period system with a mass ratio of 1.44 ± 0.06 and WD 1606+422 is a 20.1 h period system with a mass ratio of 1.33 ± 0.03. An additional object, WD 1447−190, is a 43 h period single-lined white dwarf binary, whereas WD 1418−088 does not sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…This is not surprising as low-mass white dwarfs are over-represented in magnitude-limited surveys due to their larger radii and luminosities. A caveat here is that our mass estimates for low-mass white dwarfs may be erroneous since they were based on the assumption of a single star, and that low-mass white dwarfs are usually found in binary systems (Marsh et al 1995;Kilic et al 2020). Hence, further observations would be useful for constraining the binary nature of these systems and the mass distribution below 0.5 M .…”
Section: The Da Mass Distributionmentioning
confidence: 98%
“…This is not surprising as low-mass white dwarfs are over-represented in magnitude-limited surveys due to their larger radii and luminosities. A caveat here is that our mass estimates for low-mass white dwarfs may be erroneous since they were based on the assumption of a single star, and that low-mass white dwarfs are usually found in binary systems (Marsh et al 1995;Kilic et al 2020). Hence, further observations would be useful for constraining the binary nature of these systems and the mass distribution below 0.5 M .…”
Section: The Da Mass Distributionmentioning
confidence: 98%
“…We use de-reddened GALEX FUV and NUV (Martin et al 2005), SkyMapper ugriz (Onken et al 2019), and VISTA Hemisphere Survey Y JK s photometry (McMahon et al 2021). Since the observed flux can be expressed as a combination of the individual contributions of the two components, the free parameters usually involved in this fitting process are the four atmospheric parameters T eff,1 , log g 1 , T eff,2 , log g 2 , plus the distance D (see Bédard et al 2017;Kilic et al 2020, for details). In the present case, the distance is known from the Gaia parallax, and the surface gravities can be obtained from our mass estimates together with the mass-radius relation of Althaus et al (2013).…”
Section: Binary Parametersmentioning
confidence: 99%
“…We use the same procedures as in Kilic et al (2020) to measure radial velocities for our targets. Briefly, we use a quadratic polynomial plus two Lorentzians (one for each line) to fit the H𝛼 line cores.…”
Section: Radial Velocity Measurementsmentioning
confidence: 99%
“…Trigonometric parallax measurements provide an opportunity to find SB2 white dwarfs through their over-luminosity. Bédard et al (2017) used a sample of 219 white dwarfs with parallax measurements to identify more than a dozen over-luminous white dwarfs, and Kilic et al (2020) confirmed binarity in at least nine out of 13 of these systems, including four SB2 white dwarfs. Similarly, Hollands et al (2018) analyzed the nearly complete Gaia 20 pc white dwarf sample of 139 stars, and identified several over-luminous binary candidates, including L 870-2.…”
Section: Introductionmentioning
confidence: 96%